Arbitrage in economics and elsewhere - facts well know and less known (three papers on arbitrage ideas, modeling and pricing - yesterday, today and tomorrow) - introduction to the series - Rybicki, Wojciech (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The presented series of articles on arbitrage theories and their methodological aspects consist of three papers entitled as follows: I. The Primer on Arbitrage Conceptions in Economics: Their Logics, Roots and Some Formal Models (Historical and Bibliographical Notes).II. Mathematics of Financial Arbitrage: From Algebraic Geometry at the Turn of the 19th and 20th Centuries to Modern Martingale (Generalized) Considerations III. The Arbitrage in Stochastic Finance, Social Choice Theory and Macroeconomics. The articles are devoted to present –in a historical perspective – the basic ideas and “metamorphoses” of the notion and role of an arbitrage (originated as a kind of clever and rational speculation –the last word is used in a “neutral”, not pejorative sense) as well as to point out its various, important connotations (not merely in finance or even economics) and to demonstrate some mathematical inevitable technicalities, reflecting, in fact, the logical essence and the modern view of the arbitrage (and non arbitrage) conditions.
Mathematical Economics, 2011, Nr 169-172
Keywords: arbitrage; stochastic finance; free lunch; Arbitrage Pricing Theory; martingale; cornucopia